Lexic-semantic features of some toponyms of the region of aghdam summary (Journal of Oriental Studies, 2018)
In this article the toponyms of the region of Aghdam of Azerbaijan hadbeen investigated by lexically-semantically. The investigation of toponymsof the region of Aghdam gives an understanding that this place is an ancientresident of Turkish peoples. It had been mostly proved with moreexamples of typical forms with suffixes li, lu, lar, ler. The ethimologicalexplanation of some characterical toponyms of the area of Aghdam hadbeen given, and grammatical features had been explained.